Peran Budaya dalam Membangun Hubungan Antara Umat Beragama di Suku Tenger - M Thoriqul Huda (Palita: Journal of Social Religion Research, 2019)
Indonesia is a country that has diversity in ethnicity, ethnicity, race, language, religion, and culture. However, this diversity is capable of causing conflicts both internally and externally. As with many cases that occur in Indonesia. Religion itself is a foothold, belief, and life guide, even as a scapegoat for conflicts in society. But other than the tengger tribe located in Lumajang Regency, Malang Regency, Pasuruan Regency and Probolinggo Regency, there are three religions that coexist in one village namely Islam, Hinduism and Buddhism. In the midst of pluralism, different societies of understanding and belief turned out to be able to have an attitude of tolerance and mutual respect between each other. Religious diversity is not a problem for the agrosari community to interact in carrying out daily activities. Regarding tolerance among religious people has recently become a very sticky issue among academics and the public. Local wisdom and culture are solutions to overcome this problem. Local wisdom in the Tengger tribe community is inseparable from the values of Javanese culture, as well as the cultural heritage of Majapahit which is still developing with mutual respect, tolerance, and respect for ancestral spirits and there are no striking differences in ethnicity other than differences in religious beliefs. Togetherness is manifested in the form of traditional rituals such as the Unan-Unan ceremony, Bari'an (Selamatan). Each religion has its own demands for tolerance in the Tengger tribe is ingrained, the Tengger tribe community also upholds equality and democracy in community life and respects religious leaders and dukun (sepiritual teachers) rather than administrative leaders. Because all are brothers, all families, still peaceful and harmonious, which is the mandate and ancestral heritage.